2021
DOI: 10.15252/embj.2020105712
|View full text |Cite|
|
Sign up to set email alerts
|

Cyclin D1 controls development of cerebellar granule cell progenitors through phosphorylation and stabilization of ATOH1

Abstract: During development, neural progenitors are in proliferative and immature states; however, the molecular machinery that cooperatively controls both states remains elusive. Here, we report that cyclin D1 (CCND1) directly regulates both proliferative and immature states of cerebellar granule cell progenitors (GCPs). CCND1 not only accelerates cell cycle but also upregulates ATOH1 protein, an essential transcription factor that maintains GCPs in an immature state. In cooperation with CDK4, CCND1 directly phosphory… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 61 publications
0
28
0
Order By: Relevance
“…However, our group and another have confirmed that there are ATOH1-negative populations located just beneath the ATOH1-positive cells in the EGL that, surprisingly, remain mitotic [ 59 , 60 ]. In a previous report, we also noted that the protein expression of NEUROD1, a transcription factor, was expressed in ATOH1-negative GCPs [ 9 ]. A recent study also confirmed these expression patterns in the mouse cerebellum [ 61 ].…”
Section: Transit Amplification Of Mammalian Cerebellar Granule Cell P...mentioning
confidence: 99%
See 4 more Smart Citations
“…However, our group and another have confirmed that there are ATOH1-negative populations located just beneath the ATOH1-positive cells in the EGL that, surprisingly, remain mitotic [ 59 , 60 ]. In a previous report, we also noted that the protein expression of NEUROD1, a transcription factor, was expressed in ATOH1-negative GCPs [ 9 ]. A recent study also confirmed these expression patterns in the mouse cerebellum [ 61 ].…”
Section: Transit Amplification Of Mammalian Cerebellar Granule Cell P...mentioning
confidence: 99%
“…In addition, a small number of GCPs located at the border between AT + GCPs and ND + GCPs express both ATOH1 and NEUROD1. These findings suggested that AT + GCPs give rise to ND + GCPs (called “AT-ND transition” [ 9 ]), which differentiate into GCs ( Figure 3 D), as well as the presence of a two-step amplification system of GCPs in the EGL.…”
Section: Transit Amplification Of Mammalian Cerebellar Granule Cell P...mentioning
confidence: 99%
See 3 more Smart Citations